KEMAMPUAN AWAL KOSAKATA BAHASA JEPANG PADA SISWA KELAS XII BAHASA - Agustina, Claudia; Rahayu, Nana; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research was motivated by students who had difficultyremembering Japanese vocabulary. Therefore, this research was conducted with theaim of finding out the initial vocabulary abilities of class XII Bahasa students. Thisresearch uses descriptive research with a quantitative approach. The population in thisstudy was SMAN 1 Dayun with the selected sample being class XII Bahasa. Thisresearch was conducted from in August. This research only explains how the initialJapanese language vocabulary skills of class XII are. The results of the research arethat based on the results of the tests carried out by students, the average pre-test scorewas 47.85 in the very poor category. Of the total students, there were 2 people who gota score in the good category, 2 people in the fair category, 1 person in the poorcategory and 25 people got a score in the very poor category. If you look at the overallstudent scores, the most scores in the very poor category were obtained by 25 students,this proves that the average vocabulary ability of class XII Bahasa students is stillvery low.Key Words: Japanese Vocabulary, Initial Skills